The cranial anatomy and kinesis of the bird snake Thelotornis Capensis (Smith) - Visser, J. G. J.(Jasper Gerhardus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1960.